A NeutroStructural Framework for Coordinated Development Evaluation of Land Resource Utilization and Ecological Environmental Protection - Qian Luan (Neutrosophic Sets and Systems)
Balancing land resource utilization with ecological environmental protection has become a global necessity in the face of accelerating urbanization, agriculture expansion, and climate change. Classical decision-making models often rely on binary or deterministic logic, which fails to represent the complex, uncertain, and conflicting nature of environmental and land use systems. In this study, we propose a novel NeutroStructural Decision Framework (NSDF) grounded in Neutrosophy, particularly utilizing the constructs of NeutroAlgebra and NeutroStructure, to model and evaluate the coordinated development between land exploitation and environmental sustainability. Through the formulation of NeutroTriplets ⟨T, I, F⟩ representing the degrees of truth, indeterminacy, and falsehood respectively, the model quantifies policy effectiveness across multidimensional datasets including soil integrity, land productivity, biodiversity, and urban footprint. We derive mathematical equations to compute the cumulative neutro-evaluation of any policy scenario, applying this to realistic land development examples. The results show that the NeutroStructural model captures nuanced decision outcomes far beyond traditional optimization models and highlights zones of environmental conflict, consensus, and ambiguity. This framework provides policymakers and planners with a flexible, adaptive, and robust mathematical foundation for making more informed land use decisions while safeguarding ecological systems under uncertainty.